Dancing in the streets : a history of collective joy - Ehrenreich, Barbara (Metropolitan Books, 2007)
Cultural historian Ehrenreich explores a human impulse that has been so effectively suppressed that we lack even a term for it: the desire for collective joy, historically expressed in ecstatic revels of feasting, costuming, and dancing. She uncovers the origins of communal celebration in human biology and culture. Although 16th-century Europeans viewed mass festivities as foreign and "savage," Ehrenreich shows that they were indigenous to the West, from the ancient Greeks to medieval Christianity. Ultimately, church officials drove the festivities into the streets, Protestants criminalized carnival, Wahhabist Muslims battled ecstatic Sufism, European colonizers wiped out native dance rites. The elites' fear that such gatherings would undermine social hierarchies was justified: the festive tradition inspired uprisings and revolutions from France to the Caribbean to the American plains. Yet outbreaks of group revelry persist, as Ehrenreich shows, pointing to the 1960s rock-and-roll rebellion and the more recent "carnivalization" of sports.--From publisher description.